2016
DOI: 10.1111/pim.12319
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte activation and cytokine production in Malawian children presenting with P. falciparum malaria

Abstract: SummaryMalaria in malaria‐naïve adults is associated with an inflammatory response characterized by expression of specific activation markers on innate immune cells. Here, we investigate activation and adhesion marker expression, and cytokine production in monocytes from children presenting with cerebral malaria (CM, n = 36), severe malarial anaemia (SMA, n = 42) or uncomplicated malaria (UM, n = 66), and healthy aparasitemic children (n = 52) in Blantyre, Malawi. In all malaria groups, but particularly in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
37
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 42 publications
4
37
1
Order By: Relevance
“…Interestingly, there are some apparent paradoxes between the cytokine concentrations reported in this paper and the monocyte intracellular cytokine staining (42) and immunophenotyping (6) findings that we have reported previously for the same study participants. We observed decreased IL-6 and TNF-α production by monocytes in children with different forms of malaria (42).…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…Interestingly, there are some apparent paradoxes between the cytokine concentrations reported in this paper and the monocyte intracellular cytokine staining (42) and immunophenotyping (6) findings that we have reported previously for the same study participants. We observed decreased IL-6 and TNF-α production by monocytes in children with different forms of malaria (42).…”
Section: Discussioncontrasting
confidence: 75%
“…We observed decreased IL-6 and TNF-α production by monocytes in children with different forms of malaria (42). This indicates that the elevated levels of these cytokines in serum in the current report are produced by cells other than monocytes (or macrophages), most likely T cells and NK cells.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The cause of this down regulation could not be ascertained, and it remains to be determined if this cellular phenotype is the result of an unknown immuno-modulatory process of the host or from a parasite-derived factor. It is worth noting that this same phenomenon of decreased HLA-DR expression was recently observed in monocytes obtained from Malawian children presenting at hospital with malaria [64], suggesting that this process may affect all leukocytes. Further research is certainly needed before any further inferences could be drawn.…”
Section: Discussionsupporting
confidence: 69%
“…Later it was shown that this immunological phenomenon required cooperation between antibodies and monocytes in order to be effective [41, 82, 83]. Patient data from Malawi has recently demonstrated that in patients with severe malaria, monocytes have decreased expression of activation markers compared to those from patients with uncomplicated malaria, underscoring the role that activated monocytes play in controlling morbidity [64]. …”
Section: Discussionmentioning
confidence: 99%